SARS-CoV-2 e Angiogénese: uma ligação por explicar - Gonçalo Branco Madureira (2021)
: Novel Coronavirus Disease 2019 (Covid-19) is associated with multi-systemic derangement, including circulatory dysfunction with features of endothelial dysfunction, microangiopathic thrombosis and angiocentric inflammation. Recently, intussusceptive angiogenesis has been implicated in the pathogenesis of the disease. In this article, we have broadly reviewed and discussed data regarding splitting angiogenesis including mechanisms, drivers, regulators and putative roles. We have reviewed other relevant angiogenic features in Covid-19, including their potential role in inflammation, endothelial dysfunction and permeability as well as their use as prognostic markers and therapeutical roles. We conclude that splitting angiogenesis in Covid-19 is likely the result of a combination of factors. We hypothesize that hypoxia, hypoxia-inducible factors as well as other classic angiogenic mediators, such as the Vascular Endothelial Growth Factor (VEGF) and Angiopoietins pathway, hyperinflammation and cytokine storm and dysregulation of the Renin-Angiotensin-Aldosterone System interact to promote intussusception. However, splitting angiogenesis remains poorly understood and thus further studies are needed to better characterize this phenomenon. We have also summarized the main data regarding the use of angiogenic mediators as prognostic tools. Data suggests that angiopoietins and VEGF are elevated in Covid-19 patients and are predictors of adverse outcomes. However, this is the first time that an attempt to relate these findings to intussusception was made. Finally, we reviewed the scarce data regarding angiogenic mediators as therapeutic targets in Covid-19. These preliminary findings suggest a potential benefit of bevacizumab as an add-on therapy. Whether this relates to intussusception or not requires further studies.